Breaking the continuity of the Al2O3 oxide scale by additions of Cr in Co-Al-W-based superalloys - Liang, Zhida; Pyczak, Florian; Stark, Andreas; Rao, Ziyuan; Neumeier, Steffen; Göken, Mathias (Corrosion Science, 2021)
The paper presents the effect of small amounts of Cr alloying on the oxidation behavior of a Co-9Al-9W-2Si alloy. A small amount of Cr alloying inhibits the formation of a continuous Al2O3 scale in the oxide layers. The exact mechanism is explained by studying the transient oxidation stages. Cr addition can increase the diffusion rate of oxygen in the oxidation scale. Al is consumed very fast by forming Co(Al,Cr)2O4. This impedes the formation of Al2O3. As a result, the few formed Al2O3 particles do not merge to a continuous scale in the oxide layer.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Co-based superalloys; Oxidation; Synchrotron radiation; TEM